Ukraine over the edge : Russia, the West and the "new Cold War" - Hahn, Gordon M. (McFarland & Company, Inc., Publishers, 2018)
"This study focuses on the Ukrainian crisis, from the rise of demonstrations on Kiev's Maidan Nezalezhnosti to the making of the post-revolt regime. The author sheds new light on the role of radical Ukrainian nationalists and neofascists in the February 2014 snipers' massacre, the ouster of President Yanukovych and Russia's seizure of Crimea"--